P30 Real-world tolerability study of nintedanib in patients with progressive fibrosing interstitial lung disease compared to patients with idiopathic pulmonary fibrosis. (11th November 2022) - Newman, K; Garfoot, T; Stranks, L; Morris, H; Zakis, K; Swale, J; Greaves, M; Stanel, S; Ramjug, S; Avram, C; Blaikley, J; Leonard, C; et al.
Abstract : Introduction: There are no real-world studies looking at tolerability of Nintedanib in patients who have a diagnosis of progressive fibrosing interstitial lung disease (PFILD) being treated with Nintedanib alongside immune suppressant and/or Prednisolone, comparing this to tolerability in idiopathic pulmonary fibrosis (IPF) patients. These patients were excluded from the INBUILD trial 1 . Hypothesis: Nintedanib will be less well tolerated in PFILD, compared to IPF due to immunosuppression/corticosteroid co-prescription. Methods: Retrospective study of patients treated with Nintedanib on a Named Individual Patient Supply (NIPS) by Boehringer UK for PFILD at a tertiary referral ILD specialist centre with treatment started between November 2019-January 2021. A cohort of IPF patients from our centre was used for comparison. All data was collected using hospital medical records. Tolerability and concurrent treatment data were collected from initial prescription to June 2022 for the PFILD cohort (maximum follow-up 30 months). Data for the IPF patients was collected from initial prescription until November 2017 (maximum follow-up 31 months). Results: Data from 47 PFILD patients and 51 IPF patients were compared ( table 1 ). In the PFILD cohort, 42 (89.4%) were taking Prednisolone at initiation of Nintedanib, and 26 (55.3%) were taking immunosuppression, with the most common being Mycophenolate (80.8% of patients on immunosuppressive therapy). During the follow-up, immunosuppressant doses were not required to be changed due to side effects other than infections, and 1 case of raised liver function tests. There was no statistical difference between either discontinuation rates for Nintedanib, tolerability (need to reduce the dosage), or side effect profile between both cohorts. Conclusions: This real-world study demonstrated that concurrent immunosuppression therapy did not affect the tolerability of Nintedanib in PFILD patients, therefore concerns over additive side effects may be unfounded. Useful further questions would be to assess whether there is a gender or age contribution to tolerability, whether a larger cohort would show differential hepatotoxicity, and whether the use of different immunosuppressants would have affected tolerability (the majority in this cohort took Mycophenolate). Reference: Flaherty KR, Wells AU, Cottin V, et al . Nintedanib in Progressive Fibrosing Interstitial Lung Diseases. N Engl J Med 2019; 381 (18):1718–1727.